2022
DOI: 10.3389/fcimb.2022.952297
|View full text |Cite
|
Sign up to set email alerts
|

Development of new bioactive molecules to treat breast and lung cancer with natural myricetin and its derivatives: A computational and SAR approach

Abstract: Each biopharmaceutical research and new drug development investigation is targeted at discovering novel and potent medications for managing specific ailments. Thus, to discover and develop new potent medications, it should be performed sequentially or step by step. This is because drug development is a lengthy and risky work that requires significant money, resources, and labor. Breast and lung cancer contributes to the death of millions of people throughout the world each year, according to the report of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Asp351, Ser530, and Phe404 are the common amino acid residues of PDB ID 7KCD that form maximum hydrogen bonds with ligands. The findings of Akash et al (2022) support interactions of this kind and the participation of specific amino acids in binding.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Asp351, Ser530, and Phe404 are the common amino acid residues of PDB ID 7KCD that form maximum hydrogen bonds with ligands. The findings of Akash et al (2022) support interactions of this kind and the participation of specific amino acids in binding.…”
Section: Resultssupporting
confidence: 52%
“…The online tool PASS was used to predict the antiviral, antibacterial, antifungal, and antineoplastic effectiveness of derivatives, as developed by SAR studies ( Akash et al, 2022 ). The following acquisition PASS values were obtained: Pa score 0.383–0.479 for antiviral, 0.222–0.505 for antibacterial, 0.428–0.638 for antifungal, and 0.469–0.802 for antineoplastic.…”
Section: Resultsmentioning
confidence: 99%
“…The docking studies modeling was executed to investigate the molecular interaction strategy and acquire documentation on the binding capacity and ligand effectiveness to inhibit the targeted protein. In the current study, the molecular docking analysis was evaluated with the cooperation of the PyRx AutoDock tools application, version 4.2 ( Akash et al., 2022a ; Rizvi et al., 2013 ). The automatic maximized function was used to compose the 3D grid for ligand-receptor interaction during molecular docking.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that UA has the ability to modulate a variety of signaling pathways associated with cancer survival and progression [91,92]. For example, UA reduced the expression of Stat3 and its downstream targets to inhibit the proliferation of prostate cancer and hepatocellular carcinoma [88,[93][94][95]. Results also showed that UA suppressed myeloma growth through Stat3-mediated inhibition [51].…”
Section: Discussionmentioning
confidence: 98%